Malignant melanoma—The cradle of anti-neoplastic immunotherapy. (October 2016) - Koller, Kristian M.; Wang, Wenge; Schell, Todd D.; Cozza, Eugene M.; Kokolus, Kathleen M.; Neves, Rogerio I.; Mackley, Heath B.; Pameijer, Colette; Leung, Anna; Anderson, Bryan; Mallon, Carol A.; Robertson, Gavin; et al.
Abstract: One of the defining characteristics of the malignant phenotype is the ability to evade the host immune system. Immunotherapy as a treatment modality represents a new dawn in the way we think about the treatment of a variety of malignancies. The story of immunotherapy traces its roots to its relationship with malignant melanoma. In this article, we review the intertwined history of immunotherapy and melanoma, including the early significant history, a discussion on immune mechanisms, resistance, local and systemic immunotherapeutic modalities, and speculate on possible novel future treatment options.